Receptive agrarian tax policy as panacea for low agro-innovation uptake – a socio-agricultural concern in Sub-Saharan Africa - Akor Sunday Joseph; Jacob Adetayo Adegbola; Adegbola Rukayat Queena; Oshili Moses Esho; Abdulazeez Sulyman; Sanni Lateef Oladimeji (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Although agriculture holds vast potentials for economic revolution internationally, Africa's agricultural sector and associated occupations continue to underperform. The sector is hindered by substantial challenges, including low productivity stemming from limited uptake of agricultural innovations which are now and again linked to existing unfavorable tax regimes and failed efforts to simplify tax policy in the agricultural milieu. Methods: This narative review uses comparative systematic lenses to blend existing literature while providing an objective consideration of multifaceted issues that have bearing to agricultural technology adoption and favourable tax policy. It utilizes secondary sources such as books, newspapers, archival materials, government and international organizations documents, electronic data bases, and a number of peer-reviewed journals across several disciplines to make available a well-balanced all-inclusive interdisciplinary review to highlight the importance of favourable tax policies in the quest for increase adoption of improved agricultural technologies and identifies key areas for improvement. Findings: While espousing the truism that favourable tax programs and subsidies incentivizes investment in agricultural innovations, it held that uncontrolled taxes stifle improved agricultural technology adoption. Tax incentives touted by this review to foster increase adoption include Tax Exemptions and Tax Holidays, Tax Rebates, Reduced VAT, Tax Exemption of loan Interest for banks, Concessional Import Duties, Lower Corporate Income Tax Rate, Investment Deductions, and Enhanced Capital Allowances. Beyond favourable tax policies, governments also provide subsidies that can be direct cash payments or circuitously support agricultural related operations through lessening prices of key inputs to make improved agricultural technologies more affordable. Conclusion: The paper concluded that stakeholders, especially in Africa, develop capacity to adopt and utilize innovations effectively while taking advantage of tax incentives in the agricultural milieu for improvement throughout the value chain to optimize gains from global agribusiness that could reach a trillion dollars by the end of the decade. Novelty/Originality of this article: This review is novel in its unambiguous positioning of supportive taxes and subsidies not simply as circumstantial policy instruments, but as key behavioural drivers of agricultural technology uptake. Diverging from most existing literature that treats fiscal policy incentives as auxiliary enablers or individual economic factors, this review conceptualizes taxation and subsidy regimes as direct triggers shaping innovation adoption intentions and behaviour.